Successional trends in standing dead biomass in Mediterranean basin species - Baeza, M. J.; Santana, V. M.; Pausas, J. G.; Vallejo, V. R. (Journal of Vegetation Science, 2011)
Question: Landscape models of fire occurrence in ecosystems assume that the time since the last fire determines vegetation flammability by enabling the accumulation of dead biomass. In this study we ask if Mediterranean basin shrublands respond to these models or, on the contrary, if initial successional stages in these ecosystems could be more flammable than later stages. Location: Mediterranean shrubland in the Valencia region, eastern Spain. Methods: Using different stages of vegetation development (5, 9, 14 and 26 years since the last fire), we first study the structural comiosition of the above-ground biomass in 375 individuals of nine woody species. Then, we measure how the standing dead biomass varies during succession, taking into account the surface cover of each species and the quantity of total dead biomass accumulated in different successional stages (3, 9, 14 and 26 years since the last fire). Results: The largest amount of standing dead biomass at the plant community level is observed in the middle stages of the succession. Early successional species, such as Cistus spp., Ulex parviflorus and Pinus halepensis, have a higher percentage of standing dead biomass at earlier stages in the succession than species typical of later successional stages, e.g. Juniperus oxycedrus, Quercus coccifera and Quercus ilex. Conclusions: The results suggest that monotonic increase in fire hazard with increasing stand age is not necessarily the rule in Mediterranean basin shrublands, since early successional species may accumulate large amounts of standing dead biomass and thus promote fire at early successional stages.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Early and late species; flammability; Retaining dead fuel; Species replacement; Successional stages; woody species